Development and application of a quantitative loop‐mediated isothermal amplification method for detecting genetically modified maize MON863. (27th May 2014) - Huang, Sicong; Xu, Yuancong; Yan, Xinghua; Shang, Ying; Zhu, Pengyu; Tian, Wenying; Xu, Wentao
Abstract BACKGROUND A SYBR Green I‐based quantitative loop‐mediated isothermal amplification (LAMP) assay was developed for the rapid detection of genetically modified maize MON863. A set of primers was designed based on the integration region of the Cry3Bb1 and tahsp17 genes. RESULTS The qualitative and quantitative reaction conditions (dNTPs, betaine, primers, Mg2+, Bst polymerase, temperature, reaction time) were optimized. The concentrations of Mg2+ and betaine were found to be important to the LAMP assay. The detection limits of both qualitative and quantitative LAMP for MON863 were as low as 4 haploid genomic DNA, and the LAMP reactions can be completed within 1 h at an isothermal temperature of 65 °C. CONCLUSION The results of this study demonstrate that this new SYBR Green I‐based quantitative LAMP assay system is reliable, sensitive and accurate. © 2014 Society of Chemical Industry